Peminjaman Dokumen Wajib Pajak oleh Account Representative - Waluyo, Trihadi (Simposium Nasional Keuangan Negara, 2018)
In the current process, data from new Taxpayer documents can be obtained through the inspection process so that the process of tax assessment disbursement is getting longer and more complicated. Account Representatives have space to obtain valid information or key information from Taxpayers. This space of authority in general has not been done considering that the Account Representative task has not been explicitly explained in the KUP. Whereas the use of this authority is a logical consequence of the application of Article 8 paragraph 1 of the KUP which will greatly assist the process of taxpayer development